Analysis of Educational Challenges and Character Building for Children in Facing Digital Technology in the Current Era - José Taçain (Mandalika: Jurnal Ilmu Pendidikan dan Bahasa, 2026)
This study addresses the educational challenges that children face and how these challenges relate to character building under current digital technology exposure. The research aims to describe the main educational obstacles documented in the literature and to synthesize how these obstacles are associated with character-relevant behavioral processes, particularly discipline, responsibility, and self-regulation. The method used is qualitative library research with content analysis of written sources, including books, journal articles, and scholarly reports relevant to educational challenges, digital technology, and childhood character building. The data consist of primary and secondary literature selected based on conceptual relevance to the study keywords. The study concludes that, according to the synthesized literature, unmanaged digital technology use can disrupt attention regulation, learning discipline routines, and self-regulation, thereby weakening the habituation mechanisms that support character building. However, the evidence also suggests that character outcomes can be supported when digital engagement is mediated through clear boundaries and structured educational guidance aligned with character objectives.